Digital Justice and the Right to a Fair Trial: Challenges of Videoconferencing in Criminal Proceedings - Abisheva, Saltanat; Bachurin, Sergey; Kadatsky, Sergey; Brylevskiy, Andrey; Koryakin, Ilya (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
This study examines the practice of remote criminal proceedings in Kazakhstan, with a particular focus on their compatibility with the right to a fair trial as guaranteed under international human rights law and the jurisprudence of the European Court of Human Rights (ECHR). Using a mixed-methods approach, the research combines doctrinal analysis of legal sources with case study examination of actual procedural practices in Kazakhstani courts. The findings highlight significant gaps in the Criminal Procedure Code of Kazakhstan, particularly regarding the regulation of videoconference hearings and the absence of explicit provisions addressing the accused’s objections to participating remotely. While the implementation of remote justice mechanisms is often justified as a means of improving efficiency, reducing logistical costs, and ensuring timely access to justice, these benefits cannot outweigh the fundamental principles of fairness and equality of arms. The study emphasises that involuntary participation in remote hearings may undermine effective defence rights, the immediacy of oral proceedings, and the psychological perception of justice. Ultimately, the research argues for the necessity of legislative reform that establishes clearer safeguards, ensures voluntary consent of the accused, and aligns Kazakhstan’s criminal procedure more closely with ECHR standards to strike a balance between efficiency and the protection of fundamental rights.